Principal Leadership Management in Improving Graduate Quality: A Qualitative Analysis of Indonesian Private Junior High Schools - Hilman, Fitria Faizah; Tejawiani, Ida (Journal of Innovation and Research in Primary Education, 2025)
Principal leadership management plays a crucial role in improving graduate quality within educational institutions. However, significant gaps persist between theoretical frameworks and practical implementation, particularly in resource-limited private school contexts. This study aims to analyze principal leadership management implementation across planning, organizing, implementing, and evaluating functions to identify factors affecting graduate quality improvement in Indonesian private junior high schools. This qualitative descriptive case study was conducted in two purposively selected private junior high schools in West Java, Indonesia: SMP IT Al-Istiqomah and SMP Karya Pembangunan 2 Cipongkor. Data collection employed triangulation techniques including in-depth semi-structured interviews with principals, teachers, and administrative staff, participant observation of leadership activities, and comprehensive document analysis of institutional records. Thematic analysis was utilized to identify patterns and relationships within the collected data, with validation strategies ensuring credibility, dependability, and confirmability. Findings reveal mixed effectiveness in principal leadership management implementation. Planning processes successfully establish vision and mission but lack external partnership development and systematic evaluation mechanisms. Organizational structures demonstrate clear role definition while experiencing competency-placement mismatches in 60% of key positions. Implementation shows effective operational coordination but severely limited teacher professional development, with only 30% receiving structured training annually. Evaluation practices maintain regular program assessment yet provide inadequate teacher supervision focused predominantly on administrative rather than developmental purposes. Principal leadership management demonstrates partial effectiveness across managerial functions, with significant improvements needed in external partnership development, competency-based human resource placement, systematic teacher professional development, and developmental supervision practices. Resource constraints, limited external support, and communication challenges emerge as primary obstacles requiring collaborative solutions involving multiple stakeholders to achieve optimal graduate quality outcomes.